STRUCTURAL ANALYSIS OF LEXEMES IN THE LEXICAL FIELDS OF “SUCCESS” / “MUVAFFAQIYAT” (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This dissertation investigates the structural and semantic features of lexemes within the lexical field of “success” in English and its counterpart “muvaffaqiyat” in Uzbek. Utilizing a mixed-methods approach that integrates comparative linguistic analysis, morphological decomposition, and corpus-based data, the study explores how both languages express success across different registers and cultural domains. The analysis reveals that English predominantly employs derivational affixes and analytical constructions to generate a wide network of related lexemes such as “achievement,” “victory,” nd “prosperity.” In contrast, Uzbek relies on agglutinative structures and compound forms, yielding lexemes such as “muvaffaqiyat,” “yutuq,” “gʻalaba,” and “omad,” each carrying culturally nuanced meanings. The dissertation also explores the etymology and historical evolution of core terms, their morphological formation, and their functional use in real-life communication. By comparing semantic relationships such as synonymy, antonymy, hyponymy, and collocational behavior, the study highlights both universal and language-specific strategies for conceptualizing success.